The Effect of Type A Personality and Public Accountant Law Perception on Career Interests as Public Accountants - Ni Nyoman Sri Rahayu Damayanti; I Gde Agung Wira Pertama (International Journal of Applied Business and International Management, 2021)
Individuals with type A personalities are people with high achievement-oriented, competitive, and fast workers. They are considered qualified to be public accountants. However, the perceptions of public accountant laws influence their career interests. The purpose of the research is to investigate the influence of type A personality and perception of public accountant law on career interests of accounting students as public accountants. The data were collected by disseminating questionnaires to respondents of 94 accounting students of the 7th semester and above at the private universities in Denpasar. All instruments are valid and reliable. Data distribution has been freed from classical assumptions. The findings indicate that type A personality and the perception of public accountant laws have positive and significant effects on accounting student career interests as public accountants.